Elevated receptor for activated C kinase 1 expression is involved in intracellular Ca2+ influx and potentially associated with compromised regulatory T cell function in patients with asthma. Issue 9 (September 2014) - Negoro, T.; Shimizu, S.; Narushima, M.; Banham, A. H.; Wakabayashi, H.; Takayanagi, R.; Hagiwara, T.; Roncador, G.; Osabe, T.; Yanai, T.; Kin, M.; Ikeda, K.; et al.
Summary Background Regulatory T cells (Tregs) are activated during anergy in response to T cell receptor (TCR) activation and functional immune suppression. Anergy of paediatric Tregs is partially dependent on intracellular calcium mobility; following TCR activation, Tregs do not exhibit increased intracellular Ca2+ concentration ([Ca2+]i). Objective We determined whether [Ca2+]i in adult Tregs defined their anergy, if intracellular Ca2+ movement was linked to regulatory functions, whether [Ca2+]i was indicative of asthma pathology, and the potential molecular mechanism responsible for Ca2+ movement in Tregs. Methods Tregs were purified by the magnetic bead method, and their regulatory functions were assessed by monitoring carboxyfluorescein succinimidyl ester‐labelled responder T cell proliferation. The Ca2+ response of Fura‐2‐labelled cells was measured using a video image analysis system. To analyse the functions of Tregs at the molecular level, we generated Jurkat Tet‐On® clones with doxycycline (Dox)‐induced forkhead box P3 (FOXP3) protein expression. Results CD4+CD25+CD127−/low Tregs from participants without asthma did not elicit Ca2+ influx in response to TCR activation, exhibited little proliferation and suppressed proliferation of CD4+CD25− T cells. In contrast, under similar conditions, Tregs from patients with asthma exhibited increased [Ca2+]i and robust proliferation with partial loss of regulatory functions. FOXP3 protein levels in Tet‐On® clones were high after both 2‐ and 5‐day Dox treatment; however, 5‐day cells were comparable with Tregs from patients with asthma, whereas 2‐day cells were similar to Tregs from participants without asthma. Increasing [Ca2+]i induced a high level of receptor for activated C kinase 1 (RACK1) expression in 5‐day cells. Conclusions and Clinical Relevance We confirmed that Tregs in patients with asthma are functionally impaired and that the abnormal regulatory functions of these cells can be analysed by [Ca2+]i following TCR engagement. Furthermore, the impaired functioning of Tregs evident in patients with asthma may be due to a high level of RACK1.